Glass beads discovered in the Sarmatian cemeteries from south-western Romania - Grumeza, L.; Bârcă, V. (Археологія і давня історія України, 2020)
This article analyses the glass beads discovered in the Sarmatian cemeteries from south-western Romania. Beads are the most numerous objects identified among grave goods (over 14000 specimens), being present in 43 cemeteries dated between the 2nd—4th century AD. Typologically, we identified 9 main types of monochrome beads and 8 polychrome (each with variations and different colours). Most often, beads were sewn onto apparel, being highly important for discussions concerning the fashion of the time, trading relations and Roman-Barbarian contacts.